Mechanism of adhesion of natural polymer coatings to chemically modified siloxane polymer - Joseph, Emmanuel; Rajput, Shatruhan Singh; Patil, Shivprasad; Nisal, Anuya (Langmuir, 2021)
Surface coatings play an important role in improving the performance of biomedical implants. Polydimethylsiloxane (PDMS) is a commonly used material for biomedical implants, and surface-coated PDMS implants frequently face problems such as delamination or cracking of the coating. In this work, we have measured the performance of nano-coatings of the biocompatible protein polymer silk fibroin (SF) on pristine as well as modified PDMS surfaces. The PDMS surfaces have been modified using oxygen plasma treatment and 3-amino-propyltriethoxy-silane (APTES) treatment. Although these techniques of PDMS modification have been known, their effects on adhesion of SF nano-coatings have not been studied. Interestingly, testing of the coated samples using a bulk technique such as tensile and bending deformation showed that the SF nano-coating exhibits improved crack resistance when the PDMS surface has been modified using APTES treatment as compared to an oxygen plasma treatment. These results were validated at the microscopic and mesoscopic length scales through nano-scratch and nano-indentation measurements. Further, we developed a unique method using modified atomic force microscopy to measure the adhesive energy between treated PDMS surfaces and SF molecules. These measurements indicated that the adhesive strength of PDMS-APTES-SF is 10 times more compared to PDMS-O-2-SF due to the higher number of molecular linkages formed in this nanoscale contact. This lower number of molecular linkages in the PDMS-O-2 indicates that only fewer numbers of surface hydroxyl groups interact with the SF protein through secondary interactions such as hydrogen bonding. On the other hand, a larger number of amine groups present on PDMS-APTES surface hydrogen bond with the polar amino acids present on the silk fibroin protein chain, resulting in better adhesion. Thus, APTES modification to the PDMS substrate results in improved adhesion of nano-coating to the substrate and enhances the delamination and crack resistance of the nano-coatings.